(untitled) (Raparin Journal of Humanities (RJH), 2025)
This research deals with an important aspect of civilization in Mesopotamia, which is the religious aspect that played a major role in all aspects of life, and left prominent imprints in the fields of religion, art, and thought. We have dealt with one of the important gods in religious beliefs, especially in the Akkadian era, which was represented frequently in art in all its forms. The research was limited to the sun god Shamash (Utu), represented on the cylinder seals in the Akkadian era, and his appearance between two mountains and on selected seals from the British Museum, as this scene is often represented on the Akkadian cylinder seals, and it symbolizes divine power and the cosmic order, and is linked to the idea of ​​sunrise as a daily miracle that brings light and life to the world. This scene also represents a deep mixture of cosmic beliefs and religious perceptions that embodied the Akkadian man’s vision of the cosmic order and the role of the gods in maintaining the balance between the forces of nature. Shamash appeared in it in different forms, and this is what the research will investigate and study the scene of the appearance of the god Shamash between two mountains (sunrise or sunset). The positions in which he appeared and the analysis of the main scene of the seal.